CheckMate-032 study: efficacy and safety of nivolumab and nivolumab plus ipilimumab in patients with metastatic esophagogastric cancer - Janjigian, Yelena Y.; Bendell, Johanna; Calvo, Emiliano; Kim, Joseph W.; Ascierto, Paolo A.; Sharma, Padmanee; Ott, Patrick A.; Peltola, Katriina; Jäger, Dirk; Evans, Jeffry; Braud, Filippo de; Chau, Ian; et al. (Journal of clinical oncology, 2018)
PurposeMetastatic esophagogastric cancer treatments after failure of second-line chemotherapy are limited. Nivolumab demonstrated superior overall survival (OS) versus placebo in Asian patients with advanced gastric or gastroesophageal junction cancers. We assessed the safety and efficacy of nivolumab and nivolumab plus ipilimumab in Western patients with chemotherapy-refractory esophagogastric cancers.Patients and MethodsPatients with locally advanced or metastatic chemotherapy-refractory gastric, esophageal, or gastroesophageal junction cancer from centers in the United States and Europe received nivolumab or nivolumab plus ipilimumab. The primary end point was objective response rate. The association of tumor programmed death-ligand 1 status with response and survival was also evaluated.ResultsOf 160 treated patients (59 with nivolumab 3 mg/kg, 49 with nivolumab 1 mg/kg plus ipilimumab 3 mg/kg, 52 with nivolumab 3 mg/kg plus ipilimumab 1 mg/kg), 79% had received two or more prior therapies. At the data cutoff, investigator-assessed objective response rates were 12% (95% CI, 5% to 23%), 24% (95% CI, 13% to 39%), and 8% (95% CI, 2% to 19%) in the three groups, respectively. Responses were observed regardless of tumor programmed death-ligand 1 status. With a median follow-up of 28, 24, and 22 months across the three groups, 12-month progression-free survival rates were 8%, 17%, and 10%, respectively; 12-month OS rates were 39%, 35%, and 24%, respectively. Treatment-related grade 3/4 adverse events were reported in 17%, 47%, and 27% of patients in the three groups, respectively.ConclusionNivolumab and nivolumab plus ipilimumab demonstrated clinically meaningful antitumor activity, durable responses, encouraging long-term OS, and a manageable safety profile in patients with chemotherapy-refractory esophagogastric cancer. Phase III studies evaluating nivolumab or nivolumab plus ipilimumab in earlier lines of therapy for esophagogastric cancers are underway.